2013
DOI: 10.1007/s00125-013-3112-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperglycaemia on inflammatory and stress responses and clinical outcome of pneumonia in non-critical-care inpatients: results from an observational cohort study

Abstract: Aims/hypothesis Despite the condition's high prevalence, the influence of hyperglycaemia on clinical outcomes in noncritical-care inpatients with infections remains ill defined. In this study, we analysed associations of glucose levels at admission and during initial inpatient treatment with the inflammatory response and clinical outcome in communityacquired pneumonia (CAP) patients. Methods This secondary observational analysis included 880 confirmed CAP patients. We used severity-adjusted multivariate regres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
2
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 54 publications
(56 reference statements)
5
25
2
1
Order By: Relevance
“…We found similar effects across different medical diagnoses in our heterogeneous cohort. In particular, previous studies have found similar results in acute infections and cardiovascular disease . This suggests that the association between admission hyperglycaemia and adverse outcome in people without diabetes might be independent of the underlying diagnosis.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…We found similar effects across different medical diagnoses in our heterogeneous cohort. In particular, previous studies have found similar results in acute infections and cardiovascular disease . This suggests that the association between admission hyperglycaemia and adverse outcome in people without diabetes might be independent of the underlying diagnosis.…”
Section: Discussionsupporting
confidence: 72%
“…In addition to fact that people with diabetes and hyperglycaemia were not at increased risk of mortality in our study, there was also no association between initial blood glucose levels from people with diabetes and inflammatory biomarkers in another trial . This may be explained by insulin‐induced suppression of nuclear factor kappa‐light‐chain‐enhancer of activated B‐cells (NF‐kB), which modulates expression of pro‐inflammatory cytokines .…”
Section: Discussioncontrasting
confidence: 51%
“…This association has been studied in the context of myocardial infarction, with significantly higher mortality rates reported among hyperglycaemic patients (8.4% vs 2.4%, p<0.001) 7. Similar findings have also been described, for patients with acute coronary syndrome,8 pneumonia9 and stroke 10. In addition, admission hyperglycaemia is associated with other poor outcomes, including increased length of hospital stay, hospital readmission and increased risk of infection 11 12…”
Section: Introductionsupporting
confidence: 53%
“…In non-diabetic or mixed populations, elevated admission glucose levels are common in patients with AMI and are strongly associated with an increased risk of poorer outcomes and mortality232. Acute and mean hyperglycemia during hospitalization is associated with adverse clinical outcomes2333435. Elevated admission hyperglycemia was associated with in-hospital mortality, a lower myocardial salvage index and composite MACEs in acute ST-segment elevation myocardial infarction (STEMI) patients3637383940.…”
Section: Discussionmentioning
confidence: 99%